Omnibus Law Dalam Perspektif Ketatanegaraan: Dampaknya Terhadap Struktur Kelembagaan Negara Dan Prinsip Check And Balance - Amalia Nuryanti Fatimah; Hani Aprilia Sari; Ilham Syafa Atila; Miola Salsa Biila (Shofanah Media Berkah, 2025)
Law Number 11 of 2020 on Job Creation, formulated using the omnibus law method, has brought significant changes to Indonesia's state governance system. This law is designed to simplify regulations and improve the investment climate; however, its implementation raises consequences for power relations among state institutions, the centralization of executive authority, and the shifting role of regional governments. This study aims to analyze the impact of the Omnibus Law on the state institutional structure, particularly on legislative functions, the executive, check and balance mechanisms, and regional autonomy. The research method employed is normative legal research through a statutory approach, conceptual approach, and analysis of Constitutional Court decisions. The research findings indicate that the Omnibus Law strengthens executive authority, narrows the deliberative space of the legislature, reduces regional government authority in permitting, and potentially weakens the check and balance principle. This study underscores the importance of more participatory, transparent legislative reform in line with the rule of law principle, so that regulatory effectiveness does not sacrifice the stability of Indonesia's state governance system.